Imperfect Central Bank Communication : Information versus Distraction - Orphanides, Athanasios; Dale, Spencer; Osterholm, Par. (Washington, D.C. : International Monetary Fund, 2008)
Much of the information communicated by central banks is noisy or imperfect. This paper considers the potential benefits and limitations of central bank communications in a model of imperfect knowledge and learning. It is shown that the value of communicating imperfect information is ambiguous. There is a risk that the central bank can distract the public; this means that the central bank may prefer to focus its communication policies on the information it knows most about. Indeed, conveying more certain information may improve the public's understanding to the extent that it "crowds out" a role for communicating imperfect information.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet